2018
DOI: 10.1002/1878-0261.12402
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 lethally sensitizes cancer cells to stress‐targeted therapeutic inhibitors

Abstract: In malignant transformation, cellular stress‐response pathways are dynamically mobilized to counterbalance oncogenic activity, keeping cancer cells viable. Therapeutic disruption of this vulnerable homeostasis might change the outcome of many human cancers, particularly those for which no effective therapy is available. Here, we report the use of fibroblast growth factor 2 (FGF2) to demonstrate that further mitogenic activation disrupts cellular homeostasis and strongly sensitizes cancer cells to stress‐target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Acetylation at this region is typically associated with chromatin accessibility, transcriptional activation, and cell cycle progression (Zhao & Garcia, 2015). However, cells treated with FGF-2 showed a delayed accumulation of histone H4 acetylation, most notably for the di-acetylated state, at times representing the transition between G1 and S (8-12 hrs), consistent with the delayed onset of S phase after FGF-2 treatment (Dias et al, 2019). In addition to changes in acetylation on histone H4, we also observed higher levels of tri-methylation at histone H3, lysine 27 (H3K27me3) in Y1 cells treated with FGF-2 for 24 hrs (Fig.…”
Section: Fgf-2 Delays Acetylation On Histone H4 and Promotes Repressimentioning
confidence: 70%
See 2 more Smart Citations
“…Acetylation at this region is typically associated with chromatin accessibility, transcriptional activation, and cell cycle progression (Zhao & Garcia, 2015). However, cells treated with FGF-2 showed a delayed accumulation of histone H4 acetylation, most notably for the di-acetylated state, at times representing the transition between G1 and S (8-12 hrs), consistent with the delayed onset of S phase after FGF-2 treatment (Dias et al, 2019). In addition to changes in acetylation on histone H4, we also observed higher levels of tri-methylation at histone H3, lysine 27 (H3K27me3) in Y1 cells treated with FGF-2 for 24 hrs (Fig.…”
Section: Fgf-2 Delays Acetylation On Histone H4 and Promotes Repressimentioning
confidence: 70%
“…To test this hypothesis, we treated G0-arrested Y1 cells with FBS alone or with FGF-2 and then analyzed histone PTMs at various timepoints after cell cycle progression by bottom-up mass spectrometry, which has emerged as an ideal analysis platform due to its high sensitivity, high throughput, and ability to resolve the many different types and sites of histone modifications. The timepoints chosen for analysis roughly correspond to the G1 (0.5-8 hrs), S (12-16 hrs), and G2/M (24 hrs) phases of the cell cycle based on findings with the derivative cell line Y1D1 (Dias et al, 2019). The full assortment of modifications and their relative abundances on two important regions of histone H3 (aa 27-40) and histone H4 (aa 4-17) are presented in detail in Supplemental Figs.…”
Section: Fgf-2 Delays Acetylation On Histone H4 and Promotes Repressimentioning
confidence: 99%
See 1 more Smart Citation
“…This study predicts that five EXP genes are related to rs2299939 based on the core 15-state model. Among these genes, PAPSS2 and FGF2 are related to the DNA damage repair process (Rieswijk et al, 2015;Dias et al, 2019). PAPSS2 plays an important part in sulfate assimilation and sulfate activation, during which it exhibits both ATP sulfurylase and APS kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results is in accordance with antitumor agent role of VE821 in other researches. Dias et al reported VE-821 could induced cancer cells death [39] . Another report also uncovered VE-821 induced BRCA1 Mutant Ovarian Cells death [40] .…”
Section: Discussionmentioning
confidence: 99%